Georges Dumézil og indoeuropæisk religionshistorie - Schjødt, Jens Peter (Religionsvidenskabeligt Tidsskrift, 1984)
The purpose of this article is to introduce the methods and theories of Georges Dumézil in relation to Indo-European religion and mythology. Starting with a survey of a number of important theories about the Indo-Europeans in general, and mythological research in particular, where especially the point of view of the “nature mythologists” is discussed, attention is then focused on Dumézil. After a short description of the background for his research and for some of his more important methodological viewpoints, Dumézil’s idea of the specific Indo-European ideological structure of the three functions (rulers, warriors and cattlebreeders/farmers) is presented, as well as the consequences of this research in relation to the traditional ways of treating the religion and mythology of the Indo-Europeans. Finally an attempt is made to indicate some of the importance of the “New Comparative Mythology”, not only in relation to the Indo-Europeans, but also in relation to studies of mythology and religious ideology in general.